Boarding School (Pesantren) Education During Covid-19 Pandemic at Dar El Hikmah Pekanbaru Indonesia - Syarif, Miftah; Moenada, Meimunah S (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2020)
This research was conducted with the aim of analyzing boarding school education patterns during the covid19 pandemic in Indonesia. This research uses a qualitative method of scriptive, with a case study approach that focuses on boarding school Dar El Hikmah Pekanbaru Riau, Indonesia. The source of this research data is the main informant, namely the manager and teacher of pesantren. Data collection is done with structured interviews. The results of this study showed that the pattern of education carried out in boarding school Dar El Hikmah Pekanbaru implemented a limited learning pattern, namely limiting some students to study at home and others doing learning in dormitories. The manager carries out three stages of activities, namely the stage of preparation, implementation and supervision. In the application of formal learning activities are conducted online for students who live at home, using the Google Classroom app, and e-learning. While living in a dormitory, can study offline or face-to-face with teachers, while obeying health protocols. Compliance with the rules of adhere to health protocols is done well by pesantren managers, by putting up appeals through banners, loud speakers, and 24-hour picket officers. In addition, the manager also requires all teachers and students to wear masks, provide hand washing facilities along with handshops, and prepare isolation rooms in anticipation of emergencies. The implication of this research is that pesantren always gets challenged to carry out its role and function as an Islamic educational institution, therefore openness and preparedness in reforming in various aspects of managerial needs to be put forward.